The role of N6-methyladenosine (m6A) in kidney diseases - You, Luling; Han, Zhongyu; Chen, Haoran; Chen, Liuyan; Lin, Yumeng; Wang, Binjian; Fan, Yiyue; Zhang, Meiqi; Luo, Ji; Peng, Fang; Ma, Yue; Wang, Yanmei; et al. (Frontiers in Medicine, 2023)
Chemical modifications are a specific and efficient way to regulate the function of biological macromolecules. Among them, RNA molecules exhibit a variety of modifications that play important regulatory roles in various biological processes. More than 170 modifications have been identified in RNA molecules, among which the most common internal modifications include N6-methyladenine (m6A), n1-methyladenosine (m1A), 5-methylcytosine (m5C), and 7-methylguanine nucleotide (m7G). The most widely affected RNA modification is m6A, whose writers, readers, and erasers all have regulatory effects on RNA localization, splicing, translation, and degradation. These functions, in turn, affect RNA functionality and disease development. RNA modifications, especially m6A, play a unique role in renal cell carcinoma disease. In this manuscript, we will focus on the biological roles of m6A in renal diseases such as acute kidney injury, chronic kidney disease, lupus nephritis, diabetic kidney disease, and renal cancer.